Ulcer bleeding after band ligation of esophageal varices: Risk factors and prognosis. Issue 1 (January 2020) - Dueñas, Eva; Cachero, Alba; Amador, Alberto; Rota, Rosa; Salord, Silvia; Gornals, Joan; Xiol, Xavier; Castellote, José
Abstract: Background: Post-banding ulcer bleeding is a rare complication of endoscopic band ligation of esophageal varices with high morbidity and mortality. There exist no management guidelines for this complication. Aims: To determine the incidence, outcome and risk factors of post-banding ulcer bleeding. Methods: Data for cirrhotic patients with acute variceal bleeding during a six-year period were prospectively collected, and all band ligation sessions performed were retrospectively analyzed. Demographic, analytic and endoscopic data were recorded, as well as complications, outcome and management of each episode of post-banding ulcer bleeding. Results: The study includes 521 band ligation sessions performed on 175 patients. There were 24 cases of post-banding ulcer bleeding in 21 patients (incidence 4.6%). Independent risk factors for post-banding ulcer bleeding were MELD score, hepatocellular carcinoma and total beta-blocker dose. Mortality during the bleeding episode was 23.8%. Active bleeding or adherent clots at the time of endoscopy was associated with treatment failure or death. Conclusions: Post-banding ulcer bleeding is an uncommon but severe complication of esophageal banding. Patients with hepatocellular carcinoma, poor liver function and a low beta-blocker dose have higher risk of post-banding ulcer bleeding. An aggressive treatment should be considered in case of active bleeding at endoscopy.